2014
DOI: 10.1111/rda.12356
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of 3βHSD, CYP17 and 17βHSD in the Foetal Porcine Gonads in Response to Anti‐androgen Flutamide Exposure

Abstract: We investigated whether the limited access to androgens during late prenatal period alters expression of steroidogenic enzymes involved in androgen production: 3β-hydroxysteroid dehydrogenase/Δ5-Δ4 isomerase (3β-HSD), cytochrome P450 17α-hydroxylase/17,20-lyase (CYP17) and 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1) or type 3 (17β-HSD3) in the foetal porcine gonads. Pregnant gilts were injected with anti-androgen flutamide (for seven days, 50 mg/day/kg bw) or corn oil (control) starting at 83 (GD90) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…An interesting finding is the immunolocalization of HSD17B3 within seminiferous tubules, along with Leydig cells in the interstitial compartment. It is generally considered that testicular HSD17B3 is only localized in the Leydig cell of the testis [ 24 ], and a clear positive immuno-reactivity of HSD17B3 in rat Leydig cell has been observed in the current study. However, a strong immunolocalization of HSD17B3 in rat testis has also been detected in certain germ cell types, presumably spermatocytes, of certain spermatogenic stages.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…An interesting finding is the immunolocalization of HSD17B3 within seminiferous tubules, along with Leydig cells in the interstitial compartment. It is generally considered that testicular HSD17B3 is only localized in the Leydig cell of the testis [ 24 ], and a clear positive immuno-reactivity of HSD17B3 in rat Leydig cell has been observed in the current study. However, a strong immunolocalization of HSD17B3 in rat testis has also been detected in certain germ cell types, presumably spermatocytes, of certain spermatogenic stages.…”
Section: Discussionsupporting
confidence: 73%
“…However, the specific localization of HSD17B3 in germ cells has not yet been defined. The function of HSD17B3 is responsible for the conversion of androstenedione to testosterone [ 24 ]. Thus, the existence of HSD17B3 in specific germ cells could be relevant to the production of testosterone within the seminiferous tubule, which involves local regulation for maintaining the structure and function of cells residing within the germinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed a notable decrease of 3β-HSD in adult F1 uterus and ovaries in both mRNA and protein levels, and this may explain the decrease of E 2 levels in F1 adult females. Reduction of 3β-HSD, an important steroidogenesis pathway enzyme, may affect the synthesis of E 2 , leading to abnormal changes in gonadal function [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%